ChemInform Abstract: Total Synthesis of δ‐Sanshool and Analogues Thereof. Issue 47 (3rd November 2016) - Mugnaini, Claudia; Corelli, Federico
Abstract: Based on a protected 1, 4‐butanediol‐derived core fragment, two synthetic approaches for the total synthesis of δ‐sanshool (I) and for the preparation of small libraries of analogs are presented.